Anthracene–styrene-substituted m-carborane derivatives: insights into the electronic and structural effects of substituents on photoluminescence. Issue 12 (18th May 2020) - Chaari, Mahdi; Kelemen, Zsolt; Choquesillo-Lazarte, Duane; Teixidor, Francesc; Viñas, Clara; Núñez, Rosario
Abstract : Efficient light emitters based on anthracene derivatives were developed. We prove that m -carborane is a perfect scaffold for coupling to anthracene giving rise to superb emitters in solution, while keeping the emission properties in aggregate state. Abstract : Two anthracenyl–styrenyl- m -carborane triads (one non-iodinated on B, 3, and one iodinated, 4 ) were synthesized and characterized to be further linked to octavinylsilsesquioxane (OVS) via cross-metathesis, giving rise to the corresponding hybrid materials 5 and 6 . The crystal structure of the non-iodinated heterosubstituted- m -carborane 3 was analyzed by X-ray diffraction. Transmission electron microscopy images of pristine OVS and hybrids 5–6 show important differences in the morphology of the particles; whereas OVS forms cubic-like particles, 5–6 have a spherical shape with a broad particle-size distribution. All compounds showed similar vibronic emission spectra in solution, with maxima around 415 nm, assigned to the locally excited state (LE) emission of the anthracene moiety. The similarity with the spectra of the free anthracene ( λ em = 420 nm) suggested that only small electronic interactions between the anthracene units have taken place, and there is no influence of the iodo or styrene groups on the absorption properties. This is in agreement with the DFT calculations, where calculated oscillator strength corresponding to the transitions from iodo orbitals to the LUMO are weak and could not be observed experimentally. Noticeable, triads 3–4 exhibited exceptional fluorescence quantum yield values of around 100% in solution, that are comparable to those determined for their precursors 1–2, demonstrating that the influence of the styrene group is negligible. Linking these m -carborane derivatives to the OVS led to a significant decrease of quantum yields to 34–45% for 5–6 in solution. Moreover, the PL behavior in the aggregate state was investigated and the spectra of all compounds were very similar, showing emission red-shift with maxima around 455–459 nm. Remarkably, quite high fluorescence quantum yields were determined for 3–4 (( ϕ F = 26–31%) and 5–6 ( ϕ F = 27–36%) in the aggregated state. These data confirm that the m -carborane platform enhances the quantum efficiency of the anthracene in solution, without losing the emission properties in the aggregate state. If this affirmation is associated to other scattered examples on other fluorophores also linked to m -carborane existing in the literature, the former conclusion is reinforced. m -Carborane enhances the fluorescence quantum yield of the free fluorophore, but does not alter the energy of the participating states in the photoluminescence in solution.